Strengthening Village Culture Literacy in the National Development - Burhanudin Mukhamad Faturahman; Cintantya Andhita Dara Kirana; Dedy Dwi Putra; Andri Irawan; Salesius Vitalis Kolne (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
Cultural literacy is needed as an element of development in development administration. Values in culture, especially village communities have long been a factor forming social structures in the village and are able to play a role in maintaining the preservation of environmental ecosystems. However, cultural problems in the village have long existed before the government's cultural development policies were implemented. The purpose of this paper provides a broader space to translate village culture to the lowest level into the development process because villages in the context of modernization have a vulnerability to traditions that have been carried out for generations. The research uses library research. The results of the discussion show that communication and interaction within the family contribute to strengthening local language culture and habits that are taught from generation to next generation. Culture formed by families is able to filter out social change. In addition, the diversity of cultures in the village has become a unique opportunity for the consistency of cultural development with a tolerance base amid the swift capitalism / modernization that has a universal cultural impact. Thus, these two aspects are steps in the people center development to be considered in cultural development in the village.